2020
DOI: 10.1094/phyto-02-20-0046-r
|View full text |Cite
|
Sign up to set email alerts
|

Auxin Profiling and GmPIN Expression in Phytophthora sojae−Soybean Root Interactions

Abstract: Auxin (indole-3-acetic acid, IAA) has been implicated as a susceptibility factor in both beneficial and pathogenic molecular plant-microbe interactions. Previous studies have identified a large number of auxin-related genes underlying quantitative disease resistance loci (QDRLs) for Phytophthora sojae. Thus, we hypothesized that auxin may be involved the P. sojae-soybean interaction. The levels of IAA and related metabolites were measured in mycelia and media supernatant as well as in mock and inoculated soybe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 100 publications
0
14
0
Order By: Relevance
“…We found specific and significant increase in JA accumulation in the inoculated treatment of susceptible NILs at 24 hai. It is unclear whether the accumulation of JA is due to the successful colonization of P. sojae or if, like some of our earlier studies (Stasko et al, 2020 ), increased JA aids in successful colonization by P. sojae . While our data do not show a concomitant response in SA accumulation, the clear increase in JA in response to inoculation in susceptible NILs combined with the known antagonistic relation could implicate QDRL-18 as a negative regulator of plant immunity.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…We found specific and significant increase in JA accumulation in the inoculated treatment of susceptible NILs at 24 hai. It is unclear whether the accumulation of JA is due to the successful colonization of P. sojae or if, like some of our earlier studies (Stasko et al, 2020 ), increased JA aids in successful colonization by P. sojae . While our data do not show a concomitant response in SA accumulation, the clear increase in JA in response to inoculation in susceptible NILs combined with the known antagonistic relation could implicate QDRL-18 as a negative regulator of plant immunity.…”
Section: Discussionmentioning
confidence: 67%
“…Indeed, SA, rather than JA, is generally the phytohormone associated with contributing resistance to hemibiotrophic pathogens (Robert-Seilaniantz et al, 2007 ; Pan et al, 2016 ). However, a cultivar with high levels of quantitative resistance was not affected by high levels of auxin nor its precursors; JA was proposed as playing a role in the later stages of infection (Stasko et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified a large number of auxin‐related genes that underlie QDR. For example, in the soybean– Phytophthora sojae interaction, auxin catabolite accumulation differed between a relatively resistant and a more susceptible soybean cultivar, and the ability of resistant cultivars to cope with auxin accumulation was suggested to play an important role in QDR in this pathosystem (Stasko et al ., 2020). In maize, cloning of the causal gene of the Gibberella stalk rot resistance QTL qRfg2 identified ZmAuxRP1, which encodes a plastid stroma‐localised auxin‐regulated protein, presumably modulating auxin biosynthesis (Ye et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified a large number of auxin-related genes that underlie QDR. For example in the soybean- Phytophthora sojae interaction, auxin catabolite accumulation differed between a relatively resistant and a more susceptible soybean cultivar, and the ability of resistant cultivars to cope with auxin accumulation was suggested to play an important role in QDR in this pathosystem (Stasko et al 2020). In maize, cloning of the causal gene of the Giberella stalk rot resistance QTL qRfg2 identified ZmAuxRP1, which encodes a plastid stroma-localised auxin-regulated protein, presumably modulating auxin biosynthesis (Ye et al 2019).…”
Section: Discussionmentioning
confidence: 99%